Experimental Study on Unsteady Radon Exhalation from the Overburden Layer of the Uranium Mill Tailings Pond under Rainfall - Hong Wang; Wenhua Wang; Runcheng He; Changshou Hong; Jin Wang; Xiangyang Li; Yong Liu (Science and Technology of Nuclear Installations)
In order to find out radon reduction performance of the overburden layer on uranium mill tailings (UMTs) pond beach surface after rainfall, the rainfall simulation experiment of the overburden layer was carried out with the self-developed equipment. Based on the radon migration model of the overburden layer on the UMTs pond beach surface, the change rule of radon exhalation in four types of compactness of the overburden layer within 120 hours after rainfall was studied, and the corresponding moisture content was also analyzed. The results show that the radon concentration in the overburden layer of UMTs increases nonlinearly; the dynamic change in moisture content of the overburden layer on the beach surface leads to the unsteady radon exhalation. The variation of radon exhalation shows three stages: increase, linear decrease, and stability tendency. After rainfall, radon exhalation rate increases due to water vapor and there is free radon seepage in pores. With the decrease of free radon production rate, radon exhalation rate gradually decreases until it reaches stability again. When the thickness of the overburden layer reduces, the porosity decreases with the increase in compactness of the overburden layer. While the decrease in radon reduction is more obvious, the less time it takes for radon exhalation to vary from unstable to stable overburden after rainfall.